Comparison of two methods in the treatment of congenital pseudarthrosis of clavicle: multicenter experience - Li, Jin (J Orthop Surg Res, 2021)
BACKGROUND: Congenital pseudoarthrosis of the clavicle (CPC) is an uncommon entity. Owing to its scarce presentation, treatment of this disorder has not been well established. This study aimed (1) to compare surgical treatment methods that included excision of pseudoarthrosis and iliac crest bone graft and fixate with either the elastic stable intramedullary nail (ESIN) or K-wires or plate and screws, and (2) to assess the clinical outcomes of two different surgical methods. METHODS: A multi-central retrospective study was performed between 2013 and 2017 in four tertiary teaching hospitals. Fifteen clavicles of 11 children were identified as CPC. All patients underwent pseudarthrosis resection and iliac crest bone autograft. They were divided into two groups as per the surgical treatment they underwent—plate stabilization as group A and elastic stable intramedullary nailing (ESIN) or K-wires as group B. Nine clavicles in 6 patients in group A and 6 clavicles in 5 patients in group B, were included. The Quick Disabilities of the Arm and Shoulder (QuickDASH) score was used to assess patients’ satisfaction and function following treatment at each follow-up. RESULTS: There were eight boys and three girls, with an average age of 4.7 years. All patients, except one with intellectual impairments, had radiological healing. Implant removal time was significantly shorter in group B compared to group A. No statistically significant differences existed in terms of age at surgery, time of radiological healing, complication, and clinical outcome between different groups. CONCLUSION: Surgical resection of pseudoarthrosis with an iliac crest bone graft was an effective means of surgical treatment in CPC. However, ESIN or K-wires can achieve shorter union time compared to the plate. Hence, surgical treatment is recommended for congenital pseudarthrosis of clavicular in pediatric patients. LEVEL OF EVIDENCE: Retrospective comparative study; Level III